Kajian Pencahayaan Alami dan Pencahayaan Buatan di Aula Gedung Islamic Centre Universitas Muhammadiyah Kendari - Ananda Isya Anggraeni; Ibrahim Akbar; La Pande Jurumai (LP3M Universitas Muhammadiyah Kendari, 2023)
The effect of lighting so that the application of lighting can be applied in accordance with the aesthetics of the system and its function, the aim is (1) to know more about what aspects must be considered in designing lighting in the work space, (2) as input for scientific studies and follow-up studies in efforts overcome lighting problems. The research method uses quantitative research methods. In this study, the data obtained came from the results of direct measurements and observations of the research object. more productive indoors. Seeing the application and utilization of lighting in terms of aesthetics that occurs, it is hoped that the appearance and lighting in the room will look more elegant by prioritizing the aesthetics of the building so that it is not only the allotment of good lighting functions but also the aesthetic value of a space